Kajian Teologis Yesaya 11:1-10 Sebagai Dasar Penginjilan di Era Society 5.0 - Eliman (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2025)
This paper describes the Theological Study of Isaiah 11:1-10 as the Basis for Evangelism in the era of Society 5.0 which consists of seven main points of discussion, namely the discussion about the writing of the book of Isaiah; Overview of Relationships Context Isaiah 11:1-10; Grammatical Study of the Text of Isaiah 11:1-10; Lexical Study of the Text of Isaiah 11:1-10; Theological Study Isaiah 11:1-10; The fulfillment of Isaiah 11:1-10 in the New Testament; and Application of Isaiah 11:1-10 Theological Study as a Basis for Evangelism in the era of Society 5.0. This scientific work uses a literature study approach with descriptive presentation. From the theological study of Isaiah 11:1-10 about the Prince of Peace is the person of Jesus Christ who is the Good News which is a solid, essential, essential foundation in evangelism missions, because the Gospel of Jesus Christ is still relevant in every era, especially in the era of Society 5.0 which one of the individual characteristics has spirituality which is marked by a feeling of attachment to something bigger than oneself and accompanied by an effort to find meaning in life, which can only be found in the Person of Jesus Christ as prophesied by the Prophet Isaiah in Isaiah 11:1 -10.